Tourism and Hospitality Industry During COVID-19: An Economic Perspective - Mohamed, Muharis; Patwary, Ataul Karim; Mohamed, Ahmad Edwin (iRASD Journal of Economics, 2020)
The COVID-19 pandemic has caused an ongoing tourism crisis. The most significant threat to the global economy since the Second World War is the product of unparalleled global travel constraints and residency orders. Tourism is particularly vulnerable to intervention to fight pandemics due to limited movement and social distance. Global markets, including tourist services such as world travel, domestic tourism, day trips, and parts as varied as air, cruises, transport, hotels, cafes and restaurants, conferences, festivals, meetings, or sports activities have automatically been affected by international, regional, and local travel restrictions. Leading to the dramatic stagnation of global air traffic and the fact that many countries have placed travel restrictions, closed borders, or initiated quarantine times, international and domestic tourism has reduced dramatically. Several countries have failed to return tourists home, with hundreds of thousands of people in all areas of the world participating in vital outbound markets. This study contributes to the tourism and hotel industry, particularly from an economic perspective, by reviewing related research, reports, and working papers.